Actividades y uso del tiempo de las y los jóvenes que ni estudian ni trabajan en Colombia. (2015)
This article looks for what activities young Colombians between 15 and 24 who neither study nor work (ninis) devote themselves to, and also discusses the use of their time. Specifically, gender differences were identified in major activities undertaken by both of them, emphasizing the time devoted to its implementation. To this end, the National Time Use Survey 2012-2013 was used. It was evident that there is a marked gender differentiation in the household roles by gender from an early age, since young female people are more concentrated in the work of unpaid household work and family, generating a generic polarization that increases inequality of opportunity in their present and future welfare.